Potential Source of Tree Seeds at Jering Menduyung Nature Tourism Park, West Bangka, Bangka Belitung Islands - Lestari, Yunita; Nurtjahya, Eddy; Utteridge, Timothy Michael Arthur (LenteraBio : Berkala Ilmiah Biologi, 2024)
Jering Menduyung Nature Tourism Park (NTP) still has relatively well-preserved natural areas. This area is known as Keruing Forest because of the large number of keruing hitam stands with large diameter. This study aims to identify the species that have potential to serve as seed sources in this area. Vegetation data and microclimate measurements were carried out in 21, 20 x 20 m square plots (=0.84 ha). Identification was carried out by matching specimens with the collection of Herbarium Bangka Belitungense. The species found were analyzed in reference to the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.3/MENLHK/SETJEN/KUM.1/1/2020 regarding the Implementation of Forest Plant Seeds. The results show that pules (Guioa pubescens (Zoll. & Moritzi) Radlk.) and keruing hitam (Dipterocarpus grandiflorus (Blanco) Blanco) can be used as source of identifiable seeds stands. Both species have seedlings that grow in clusters near their parent tree. However, due to insufficient spacing between parent trees, they do not meet the utilization requirements outlined in the SNI 8806:2019 Source of forest tree propagules, these two species cannot be used as natural seed sources. Vegetative propagation or a policy review can be considered as alternative solutions.